Characterization and Phytochemical Screening Of Tampala Bajakah Wood (Spatholobus littoralis Hassk) Extract With Methanol and Ethyl Acetate Solvents - Alviana, Liya; Ridwanto, Ridwanto; Daulay, Anny Sartika; Rani, Zulmai (Indonesian Journal of Science and Pharmacy, 2024)
One of the plants that contains secondary metabolite compounds is Bajakah Tampala wood (Spatholobus littoralis Hassk). The aim of this research is to determine the chemical compounds contained in methanol and ethyl acetate extracts. The stages of this research include processing plant materials, making methanol and ethyl acetate extracts, characterization examinations, and phytochemical screening. Bajakah Tampala wood extract was made using the maceration method using methanol and ethyl acetate. The extract obtained was concentrated using a rotary evaporator. The characterization of Bajakah Tampala sawdust showed that the water content test was 2%, the water soluble juice content test was 7.1%, the ethanol soluble juice content test was 12.05%, the total ash content test was 3.65%. , and testing the ash content that is insoluble in acid was 0.1%. Meanwhile, the results of the phytochemical screening of Bajakah Tampala wood showed that it contained chemical compounds such as alkaloids, flavonoids, saponins, tannins, and steroids and triterpenoids.